Top down modulation of attention to food cues via working memory. - Higgs, S; Rutters, F; Thomas, J; Naish, K; Humphreys, G (2012)
Attentional biases towards food cues may be linked to the development of obesity. The present study investigated the mechanisms underlying attentional biases to food cues by assessing the role of top down influences, such as working memory (WM). We assessed whether attention in normal-weight, sated participants was drawn to food items specifically when that food item was held in WM. Twenty-three participants (15 f/8 m, age 23.4±5 year, BMI 23.5±4 kg/m(2)) took part in a laboratory based study assessing reaction times to food and non-food stimuli. Participants were presented with an initial cue stimulus to either hold in WM or to merely attend to, and then searched for the target (a circle) in a two-item display. On valid trials the target was flanked by a picture matching the cue, on neutral trials the display did not contain a picture matching the cue, and on invalid trials the distractor (a square) was flanked by a picture matching the cue. Cues were food, cars or stationery items. We observed that, relative to the effects with non-food stimuli, food items in WM strongly affected attention when the memorised cue re-appeared in the search display. In particular there was an enhanced response on valid trials, when the re-appearance of the memorised cue coincided with the search target. There were no effects of cue category on attentional guidance when the cues were merely attended to but not held in WM. These data point towards food having a strong effect on top-down guidance of search from working memory, and suggest a mechanism whereby individuals who are preoccupied with thoughts of food, for example obese individuals, show facilitated detection of food cues in the environment.